The extremely low-frequency electromagnetic field (50 Hz) can establish a new “set-point” for the activity of the locus coeruleus–noradrenergic (LC-NA) system in rat - Angelika Klimek; Hanna Kletkiewicz; Agnieszka Siejka; Joanna Wyszkowska; Justyna Maliszewska; Maciej Klimiuk; Milena Jankowska; Justyna Rogalska (Brain Research Bulletin)
Exposure of organisms to extremely low-frequency electromagnetic field (ELF-EMF; 50 Hz) has been increasing in recent decades, which is connected with dynamic technological development. ELF-EMF is considered a stress factor and its effects on organisms are still being investigated. We aimed to determine its impact on the locus coeruleus–noradrenergic (LC-NA) system enabling adaptation to stressful conditions. For this purpose, we exposed rats to 50 Hz ELF-EMF of 1 and 7 mT, 1 h/day for 7 days. The procedure was repeated three times to examine the organism's adaptive capabilities. Subsequently, the concentration of adrenaline, noradrenaline and its metabolite MHPG as well as the expression of the β2-adrenergic receptor was assessed. After the end of each exposure, part of the animals were subjected to a behavioural test to assess the influence of repeated ELF-EMF exposure on stress response to subsequent stress factors. Our research proved that mechanisms underlying the effects of ELF-EMF on stress response include the LC-NA system. ELF-EMF of 1 mT induced adaptive changes in the NA-LC system. However, exposure to 7 mT caused increased activity of the stress system which resulted in sensitization to subsequent, heterotypic (different from the one previously acting) stress factor. As ELF-EMF of 7 mT caused a profound decrease in β2-AR level would strongly inhibit the potential for neuroplastic processes in the hippocampus. Moreover, rats exposed to ELF-EMF of 7 mT showed moderately increased anxiety-related behaviour. Disturbances in NA-LC transmission may underlie the development of some neurodegenerative and psychiatric diseases which indicates the possible involvement of ELF-EMF in the pathogenesis of these disorders.